Evaluation of continuous flow centrifugation as an alternative technique to sample microplastic from water bodies. (October 2019) - Hildebrandt, L.; Voigt, N.; Zimmermann, T.; Reese, A.; Proefrock, D.
Abstract: The scientific and public interest regarding environmental pollution with microplastic has considerably increased within the last 15 years. Nevertheless, up to now there is no widely applied standard operation procedure for microplastic sampling, resulting in a lack of inter-study comparability. In addition, many studies on microplastic occurrences do not indicate a sound methodological validation of the applied methods and procedures. This study presents an alternative volume-reduced sampling technique to sample the entire load of suspended particulate matter including microplastic particles in natural waters, based on continuous flow centrifugation. For the lab-scale validation of the proposed instrumental setup, six different microplastic types (PE, PET, PS, PVDC, EPS and PP) were used. The particles covered a size range from 1 μm to 1 mm and a density range from 0.94 g mL - 1 to 1.63 g mL - 1 . Recoveries ranged from 95.0% ± 2.3% - 99.1% ± 0.3% for virgin powders and from 96.1% ± 0.6% - 99.4% ± 0.2% (1 SD, n  = 2 - 3) for microplastic suspended in river water for 40 days. Gravimetric and microscopic analysis of the effluent indicates efficient removal of microplastic from the suspensions. Static light scattering analysis of the microplastic suspensions prior to and after centrifugation confirmed that no change of the particle size distribution has occurred – neither through aggregation nor through size-discrimination during centrifugation. Moreover, the system was tested in the field and used twice to sample suspended particulate matter from the Elbe estuary directly on site. Based on these first lab-scale experiments, continuous flow centrifugation proves a promising technique bearing potential to alleviate drawbacks such as contamination, filter clogging and particle size-discrimination of commonly used volume-reduced microplastic sampling approaches. Graphical abstract: Image 1 Highlights: A new non-size-discriminating sampling technique for small microplastic in water was validated. Quantitative recovery for six different microplastic types was achieved. The used small microplastic particles covered a broad size and density range. Positively and negatively buoyant microplastic can be sampled. Virgin and microplastic suspended in riverine water were retained.